2010
DOI: 10.1303/aez.2010.465
|View full text |Cite
|
Sign up to set email alerts
|

Non-crop host plants of Tetranychus spider mites (Acari: Tetranychidae) in the field in Okinawa, Japan: Determination of possible sources of pest species and inference on the cause of peculiar mite fauna on crops

Abstract: The species composition of spider mites on crops in Okinawa is peculiar in that Tetranychus okinawanus and T. piercei are dominant on most islands, whereas T. urticae (green form) and T. kanzawai are not. To determine the source plants of Tetranychus species infesting crops, as well as to contribute to our understanding of the cause of this peculiar mite fauna, we collected Tetranychus mites on non-crop plants throughout Okinawa (more than 450 sites on 15 islands) and identified them. Except in the case of T. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 13 publications
0
11
0
1
Order By: Relevance
“…New distribution records of mite species were determined by referring to Ehara and Amano (2004) and Ehara (2007). Most of the co‐occurring spider mite species have already been identified, but some were newly identified in the present study (see Ohno et al . 2009, 2010).…”
Section: Methodsmentioning
confidence: 66%
See 1 more Smart Citation
“…New distribution records of mite species were determined by referring to Ehara and Amano (2004) and Ehara (2007). Most of the co‐occurring spider mite species have already been identified, but some were newly identified in the present study (see Ohno et al . 2009, 2010).…”
Section: Methodsmentioning
confidence: 66%
“…New distribution records of mite species were determined by referring to Ehara and Amano (2004) and Ehara (2007). Most of the co-occurring spider mite species have already been identified, but some were newly identified in the present study (see Ohno et al 2009Ohno et al , 2010. The raw collection and species identification data used in the present study are presented in Appendix S1 in Supporting Information.…”
Section: Introductionmentioning
confidence: 91%
“…Although the two spider mite species co-occur on the same host plants (Kondo and Takafuji 1985;Morishita 1992Morishita , 1997Takafuji and Morishita 2001;Osakabe et al 2002;Ohno et al 2010) and have the potential to live closely together on a single leaf, as demonstrated here, strong natural selection for heterospecific cooperation (in comparison to conspecific cooperation) remains questionable. The apparent cooperation between heterospecifics may rather be a byproduct of cooperation between conspecifics that live together.…”
Section: Discussionmentioning
confidence: 84%
“…They live together on dozens of wild and cultivated host plant species and often co-occur on the same plant specimen (Kondo and Takafuji 1985;Morishita 1992Morishita , 1997Takafuji and Morishita 2001;Osakabe et al 2002;Ohno et al 2010). Mated mite adult females (founder individuals) construct complicated, irregular webs on leaf surfaces (Saito 1983), feeding and reproducing inside the webs, and ultimately forming aggregations that include juveniles that also contribute to the web building (Hazan et al 1974;Clotuche et al 2009).…”
Section: Communicated By J Choementioning
confidence: 99%
“…'Genus unknown' indicates a species that was not identified due to lack of adult specimens. A newly recorded host for each mite species is denoted with an asterisk [determined by referring to Migeon andDorkeld (2006-2010) and Ohno et al (2010Ohno et al ( , 2011. Oligonychus modestus and Tetranychina harti were newly found on Miyako Island.…”
mentioning
confidence: 99%